Inovasi Produk Serbuk Jahe, Nastar Siwalan dan Sabun Cuci Tangan Lidah buaya di Desa Prunggahan Kulon Kecamatan Semanding Kabupaten Tuban - Dede Mariyani; Hariyanti Hariyanti; Rokhadi Rokhadi; L. Happy Amira; Sukistanto Sukistanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Many things are found in the market with various brands and forms, such as in liquid form, instant powder or tablets. The tendency of people today is to prefer to use products whose packaging and presentation are more practical and fast, because it does not need to require a lot of time in preparing it. One example of a health drink that can be found is ginger extract instant drink, where the product is generally made by taking the juice from the ginger rhizome and then further processing. Most of these products are found in powder form, while some are made in tabled or water form.